Approximation and Simulation of Signal Belonging to the Generalized Weighted Lipschitz Class by ...: Aproximación y Simulación de Señal Perteneciente a la Clase de Lipschitz Generalizada Ponderada ... (BISTUA Revista de la Facultad de Ciencias Básicas, 2024)
In this study, the well-known Fourier Conjugate series, which is traditionally summable through various individual methods, demonstrates enhanced convergence speed and improved signal approximation when subjected to a product transform. This work aims to establish a novel theorem for approximating signals within a specific function class, utilizing product summability of conjugate Fourier series. Additionally, a range of illustrative examples is provided to validate the proposed summability method and highlight their convergence behavior. The findings are further supported through simulations conducted using MATLAB programming.
Keywords: Generalized weighted Lipschitz class; Conjugate Fourier series; Holder inequality